2019
DOI: 10.4097/kja.d.18.00238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexamethasone and hydrocortisone on rocuroniuminduced neuromuscular blockade and reversal by sugammadex in phrenic nerve-hemidiaphragm rat model

Abstract: Background The facilitator effects of steroids on neuromuscular transmission may cause resistance to neuromuscular blocking agents. Additionally, steroids may hinder sugammadex reversal of neuromuscular blockade, but these findings remain controversial. Therefore, we explored the effect of dexamethasone and hydrocortisone on rocuronium-induced neuromuscular blockade and their inhibitory effect on sugammadex. Methods We explored the effects of steroids, dexamethasone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…The assessment of evidence was based on study design, risk of bias, inconsistency, indirectness, imprecision, and other considerations using GRADEpro GDT. 15…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of evidence was based on study design, risk of bias, inconsistency, indirectness, imprecision, and other considerations using GRADEpro GDT. 15…”
Section: Discussionmentioning
confidence: 99%
“…The presynaptic effects have been observed during short-term treatment. Synthesis and increased release of acetylcholine have been observed [7].…”
Section: Discussionmentioning
confidence: 99%
“…We did not estimate the sample size statistically. Previous studies have conducted experiments with about 10 animals per group to achieve statistically signi cant results [5][6][7]. In a previous study that investigated the effects of dexamethasone on sugammadex reversal in rocuroniuminduced NMB in animals, it was suggested that 10 animals in one group are su cient to produce signi cant results [6,8,9].…”
Section: Animals and Group Assignmentsmentioning
confidence: 99%